(untitled) (Archives of Mechanics - Test, 2010)
In this paper, the steady mixed convection boundary layer flow about a solid sphere, generated by Newtonian heating in which the heat transfer from the surface is proportional to the local surface temperature, is considered. The governing boundary layer equations are first transformed into a system of non-dimensional equations via the non-dimensional variables, and then into non-similar equations before they are solved numerically, using an implicit finite-difference scheme known as the Keller-box method. Numerical solutions are obtained for the skin friction coefficient and the wall temperature, as well as the velocity and temperature profiles with several parameters considered, namely the mixed convection parameter λ, the Prandtl number Pr and the conjugate parameter γ.